Depression - an interdisciplinary problem of modern nursing. Case study - Machul, Michał; Pawłowski, Piotr; Kościołek, Aneta; Jakubowska, Klaudia (Journal of Education, Health and Sport, 2019)
Introduction. Depression has become a civilization illness in recent years. Epidemiological data show an upward trend in the incidence of this illness, being often of unknown causality. Treatment of depression is multi-faceted, focused on minimizing the symptoms of the illness and psychological support. The nurse as a member of a therapeutic team is required to perform specific professional roles, i.e. therapeutic, remedial, educational, preventive and that of health promotion.Aim of the study. The aim of the study was to define the nurse's tasks regarding a patient with depression.Materials and methodology. The study was based on the case study method. An interview, nursing observation, measurement and documentation analysis were used as study techniques, and the study tools applied comprised: patient data collection guide, Beck Depression Inventory (BDI), Scale of Acceptance of Illness (AIS), The Nurses' Global Assessment of Suicide Risk (NGASR), MSE (Mental Status Examination) test, Body Evaluation Esteem Scale (BES).Findings. During the research process, 11 NANDA nursing diagnoses were determined regarding the patient's health problems. Due to the specificity and the course of the illness, the nursing plan, based on NIC, focuses more on the patient's mental state than on the aspects of somatic origin.Conclusions. The physical, social and mental condition of the patient with depression depends on the severity of the illness. Nursing problems result from the found clinical symptoms of the illness. The use of NNN (NANDA, NIC, NOC) allows the use of nursing interventions based on scientific evidence.